Widespread release of dissolved organic carbon from anoxic boreal lake sediments. Issue 2 (3rd April 2017) - Peter, Simone; Agstam, Oskar; Sobek, Sebastian
Abstract: Sediments in boreal lakes are important components of the carbon cycle because they receive and store large amounts of organic carbon (OC) and at the same time are a source of greenhouse gases. Under anoxic conditions, sediment OC can be lost through dissolution from the solid phase and subsequent diffusion to the water column. Although this process may have implications for sediment OC budgets, it has yet to be studied systematically. We combined laboratory sediment incubation experiments from 4 boreal lakes in central Sweden that differed widely in their biogeochemical conditions with data from the Swedish monitoring program covering >100 lakes to analyze the frequency of occurrence of sediment DOC loss in boreal lakes and identify lake characteristics and the conditions related to high DOC fluxes from anoxic sediments. We found DOC diffusion from anoxic sediments in all the anoxic sediment incubations but at different mean rates (0.7–3.7 mmol m −2 d −1 ). Similarly, 16 of 17 of the monitoring lakes that developed anoxic bottom water exhibited an increase in bottom-water DOC concentration, corresponding to a mean (and standard deviation) DOC diffusion flux from anoxic sediment of 11.1 (35.4) mmol m −2 d −1 . The observed variability between lakes was related to particularly large DOC fluxes in humic-rich lakes, which we attribute to their low pH and high share of terrestrial OC favoring the formation of OC-iron aggregates. Accordingly, increasing pH might facilitate the dissolution of sediment OC because high dissolved OC fluxes from anoxic sediments were accompanied by high microbial iron and sulfate reduction, resulting in concomitant pH increase.